Jackpot summer [large type] - Friedland, Elyssa (Thorndike Press large print top shelf., 2024)
"The four Jacobson children were raised to respect the value of a dollar. Their mother reused tea bags and refused to pay retail; their father taught them to budget before he taught them to ride a bike. And yet, now that they're adults, their financial lives are in disarray. The siblings reunite when their newly widowed father puts their Jersey Shore beach house on the market. Packing up childhood memories isn't easy, especially when there's other drama brewing. Matthew is miserable at his corporate law job and wishes he had more time with his son; Laura's marriage is imploding in spectacular fashion; Sophie's art career is stalled while her boyfriend's is on the rise; and Noah's total failure to launch has him doing tech repair for pennies. When Noah sees an ad for a Powerball drawing, he and his sisters go in on tickets while their brother Matthew passes. All hell breaks loose when one of the tickets is a winner and three of the four Jacobsons become overnight millionaires. Without their mother's guidance, and with their father busy playing pickleball in a Florida retirement village, the once close-knit siblings search for comfort in shiny new toys instead of each other. It's not long before the Jacobsons start to realize that they'll never feel rich unless they can pull their family back together"--